Historical Connections and Economic Relations of Croatia towards Germany and Austria - Anita RADMAN PEŠA; Jurica BOSNA; Zdenko PROHASKA (Communications of International Proceedings, 2020)
We measured the economic activity and stock exchanges of Germany and Austria as developed countries, and compared it with Croatia, the newest EU country, in order to demonstrate the level and direction of economic integration and historical connections. Economic integration has been researched by ARCH models in which dependent variables are stock market indices and undependent variables main macroeconomic indicators. Traditionally, Croatia has been dependent on the German and Austrian economies, due to good economic and political connections in the past. The empirical findings obtained in application of ARCH method from 2000 to 2018 provide evidence of economic integration of Croatia with Germany and Austria, but in a somewhat lesser extent. Austria has strong economic connections with Germany, while the process of economic integration of the Republic of Croatia has not yet been completed. The slower economic integration of the Republic of Croatia demonstrates still insufficient economic development, the exigency to continue reforming and to achieve effective economic growth.
Keywords: Economic integration; stock market volatility; EU entry; ARCH methodology.